2016
DOI: 10.1021/acs.analchem.6b04350
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Fast Humidity Sensor Based on A Redox Conducting Supramolecular Ionic Material for Respiration Monitoring

Abstract: Real-time monitoring of respiratory rate (RR) is highly important for human health, clinical diagnosis, and fundamental scientific research. Exhaled humidity-based RR monitoring has recently attracted increased attention because of its accuracy and portability. Here, we report a new design of an exhaled humidity sensor for the real-time monitoring of the RR based on a synthetic redox conducting supramolecular ionic material (SIM). The humidity-dependent conducting SIM is prepared by ionic self-assembly in aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
(53 reference statements)
1
31
0
1
Order By: Relevance
“…The thickness of the NP film is approximately 400 nm from line profiles in Figure S1. The scanning electron microscope image of a NP film and a graphite electrode is shown in Figure S1 For evaluating dynamic response of resistance of SiO2 NP films, we used a saturated KCl solution in a closed vessel which had 84 % RH 41,42 . We monitored resistance of the films while taking the sensor into and out of the vessel.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness of the NP film is approximately 400 nm from line profiles in Figure S1. The scanning electron microscope image of a NP film and a graphite electrode is shown in Figure S1 For evaluating dynamic response of resistance of SiO2 NP films, we used a saturated KCl solution in a closed vessel which had 84 % RH 41,42 . We monitored resistance of the films while taking the sensor into and out of the vessel.…”
Section: Methodsmentioning
confidence: 99%
“…For that, Agcayazi et al [ 123 ] used a mannequin equipped with an inflatable cuff bladder that emulated breathing cycles, which is similar to the prototype of Koch et al [ 90 ]. For humidity sensors, authors designed controlled humidity chambers using humidifiers and dry air compressors [ 74 ] or switches for controlling nitrogen flow and a motor to control the dispersion of water vapor [ 97 ]. Finally, other studies presented artificial validation prototypes adapted to the specific sensors used for respiration monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…It was called “human observation”, since an expert provided a value of the breathing parameter from direct observation of the signals recorded by the sensors. Figure 28 shows that validation using a reference device was the predominant approach (adopted by 67% of the studies that performed validation), followed by the use of an artificial validation prototype (10%) [ 69 , 74 , 77 , 90 , 93 , 97 , 110 , 114 , 116 , 119 , 123 , 135 , 141 , 146 , 150 , 226 ]. It is also worth noting that 53 studies presented the sensing systems without providing evidence of their validation.…”
Section: Resultsmentioning
confidence: 99%
“…Humidity measurements are critical in a wide range of applications such as climatology, agriculture, architecture, and human comfort . So far, various humidity sensors built on different transduction mechanisms have been proposed and developed . Thanks to their rich surface chemistry and structure designability, carbon materials are considered to be particularly attractive in humidity sensing.…”
Section: Ultrafast and Sensitive Humidity Sensingmentioning
confidence: 99%
“…[59] So far,v arioush umiditys ensors built on different transduction mechanisms have been proposed and developed. [60,61] Thankst ot heir rich surfacec hemistry and structure designability,carbon materials are considered to be particularly attractive in humidity sensing.In2012, Nair et al demonstrated the selective superpermeability of the GO membrane to water molecules, [53a] suggesting applications such as humidity sensing. As the aqueous solution of GO turned out to be acidic, [62] protons generated throught he reaction of water molecules with the GO surface functional groups result in ad ecrease in the electrical impedance.P reviously,t he measured proton con- Figure 5.…”
Section: Ultrafast and Sensitive Humidity Sensingmentioning
confidence: 99%